Distinctive characteristics of early-onset and late-onset neuromyelitis optica spectrum disorders. (3rd April 2017) - Zhang, Lin-Jie; Yang, Li-Na; Li, Ting; Wang, Jing; Qi, Yuan; Zhang, Da-Qi; Yang, Chun-Sheng; Yang, Li
ABSTRACT: Objectives : Little is known about patients with neuromyelitis optica spectrum disorders (NMOSD) as defined by onset age. This study aimed to analyze the different demographic, clinical, laboratory, and magnetic resonance imaging (MRI) characteristics in early-onset (≤50 years) NMOSD (EONMOSD) and late-onset (>50 years) NMOSD (LONMOSD). Materials and Methods : We enrolled 142 patients with NMOSD from Tianjin Medical University General Hospital, Tianjin, China, and categorized them into two groups according to the age of onset: EONMOSD and LONMOSD. Demographic, clinical, laboratory, and MRI characteristics were collected and compared between the two groups. Serum aquaporin-4 (AQP4) antibody levels were determined by cell-based assay and fluorescence immunoprecipitation assays. Results : Among the patients studied, 83 had early onset (≤50 years) and 59 had late onset (>50 years) of NMOSD. As compared with LONMOSD, EONMOSD patients had more severe visual disability according to functional scores in clinical parameters, significantly lower C3 and C4 serum levels, more frequent cervical lesions, and more lesions around the fourth ventricle, but fewer lesions in hemispheric white matter. LONMOSD patients suffered more motor and sensory disability than EONMOSD patients. Conclusions : In NMOSD, the clinical, laboratory, and MRI features differ according to age of onset, suggesting that differences in pathogenesis and treatment should be further investigated.